2002
DOI: 10.1046/j.1472-765x.2002.01063.x
|View full text |Cite
|
Sign up to set email alerts
|

The ineffectiveness of organic acids, freezing and pulsed electric fields to control Escherichia coli O157:H7 in beef burgers

Abstract: Aims: The objective of this study was to investigate the potential value of individual and combined applications of some GRAS (generally regarded as safe) additives with freezing and pulsed electric field (PEF) application, in reducing the risks associated with the presence of E. coli O157:H7 in beef burgers. Methods and Results: Beef burgers, trimmings and filter paper were inoculated with E. coli O157:H7 and subjected to a range of chemical and physical treatments. Sequential application of 2% (v/v) lactic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Several studies reported contradictory findings regarding the use of PEF in meat and meat products (Keklik et al 2010). In this context, Bolton et al (2002) stated that use of pulse electric field was not effective in controlling E. coli O157:H7 growth in beef. The reason behind that incapability may be due to low voltage and high protein and fat contents of beef.…”
Section: Pulsed Electric Fieldmentioning
confidence: 99%
“…Several studies reported contradictory findings regarding the use of PEF in meat and meat products (Keklik et al 2010). In this context, Bolton et al (2002) stated that use of pulse electric field was not effective in controlling E. coli O157:H7 growth in beef. The reason behind that incapability may be due to low voltage and high protein and fat contents of beef.…”
Section: Pulsed Electric Fieldmentioning
confidence: 99%
“…No significant inactivation nor sub-lethal injury of Listeria innocua was observed. The absence of microbial inactivation during conventional freezing has been reported for various micro-organisms (Bolton et al, 2002;Dykes & Moorhead, 2001;Moorhead & Dykes, 2002;Novak & Juneja, 2003).…”
Section: Surface (T ) Undercoolingmentioning
confidence: 99%
“…Bolton et al (2002) studied the inactivation of E. coli O157:H7 by freezing beef burgers (at À20 C for 2 h). No significant reduction of bacterial counts was observed.…”
Section: Microbial Resistance To Freeze-thaw At Atmospheric Pressure mentioning
confidence: 99%